Answer:
![( {x}^{2} - 10x) - ( - 5 {x}^{2} + x) \\ {x}^{2} - 10x + 5 {x}^{2} - x \\ \boxed{6 {x}^{2} - 11x}](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%20-%2010x%29%20-%20%28%20-%205%20%7Bx%7D%5E%7B2%7D%20%20%2B%20x%29%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20-%2010x%20%2B%205%20%7Bx%7D%5E%7B2%7D%20%20-%20x%20%5C%5C%20%20%5Cboxed%7B6%20%7Bx%7D%5E%7B2%7D%20%20-%2011x%7D)
<h3>(6x²-11x) is the right answer.</h3>
Answer:
600
Step-by-step explanation:
200*3=600
Answer:
(-4x - 2)(-5x) + (-4x - 2)(3)
Step-by-step explanation:
Your polynomial is
(-4x - 2)(-5x + 3)
The distributive property states that
a(b + c) = ab + ac
Let a = -4x - 2. Then
(-4x - 2)(-5x + 3) = a(5x + 3) = a(-5x) + a(3)
Substitute the value of a.
a(-5x) + a(3) = (-4x - 2)(-5x) + (-4x - 2)(3)
You have just distributed the first binomial (-4x - 2) among the terms of the second binomial.
Answer:
0=0
Step-by-step explanation:
6(2x+4)=4(3x+6)
Step 1: Simplify both sides of the equation.
6(2x+4)=4(3x+6)
(6)(2x)+(6)(4)=(4)(3x)+(4)(6)(Distribute)
12x+24=12x+24
Step 2: Subtract 12x from both sides.
12x+24−12x=12x+24−12x
24=24
Step 3: Subtract 24 from both sides.
24−24=24−24
0=0